e-Runner: A mobile application for campus food delivery service / Jiwa Noris Hamid, Ammar Adnan and Hawa Mohd Ekhsan - Hamid, Jiwa Noris; Adnan, Ammar; Mohd Ekhsan, Hawa (UiTM Cawangan Perlis, 2022)
Nowadays, technology has played a vital role in revolutionizing the food delivery service and benefits the students, runners, and food outlets in many ways. Life as a student is known to be challenging due to academic load, assignment deadlines, bouncing back and forth to class, extra-curricular activities, etc. This is a typical daily scenario on campus that require good time management. In the preliminary investigation of this study, students prefer to take away their food and dine in their rooms so that they will not waste their time by spending too much time in the cafeteria. It is found that convenience is the prime factor for the students as the orders can be made as simple as a few clicks on any mobile device, and the food and beverages are delivered to their doorstep. Additionally, this can prevent them from spending too much or wasting time buying food. Since food delivery becoming popular and preferable recently, thus, this study is aimed to develop a mobile application named e-Runner for the campus food delivery system. Students can make a food order, check the order status, and view a variety of food and beverages from several food outlets. The modified Waterfall Model has been used as the methodology of this study and consists of 4 phases, namely Requirement Analysis, Design, Implementation, and Testing. The application has been tested using two types of testing; Functionality and Usability Testing. The testing results show that this application has many benefits, such as saving time, convenience and act as an all-in-one platform. Furthermore, it can enhance students' lifestyles and can improve customer experience.